Features of construction processes of reconstruction in the conditions of internal construction of objects - Savyovsky, V.; Solovey, D. (Ways to Improve Construction Efficiency, 2019)
The article is devoted to the actual problem of performing construction work in conditions of internal constraint in the reconstruction of industrial buildings. The presented example of performance of work on a specific object clearly demonstrates the impact of this feature on the development of both constructive and organizational and technological solutions. The method of determining the numerical values and the degree of influence of the factor of internal constraint on the technical and economic indicators of the work on the reconstruction of existing buildings is presented. This makes it possible to forecast technical and economic indicators and select effective work solutions at the stage of developing design and estimate documentation, when developing investment projects for the reconstruction of buildings, and also in the process of engineering preparation of construction when developing work projects. Lighting the practical experience gained will provide a basis for improving the technology and organization of work in the reconstruction of similar objects.